High‐efficiency single etch step apodized surface grating coupler using subwavelength structure. Issue 6 (13th October 2014) - Benedikovic, Daniel; Cheben, Pavel; Schmid, Jens H.; Xu, Dan‐Xia; Lapointe, Jean; Wang, Shurui; Halir, Robert; Ortega‐Moñux, Alejandro; Janz, Siegfried; Dado, Milan
<x xml:space="preserve">Abstract</x> It is experimentally demonstrated that a high coupling efficiency can be achieved for an arbitrary buried oxide thickness by judicious adjustment of the grating radiation angle. The measured coupling loss of a continuously apodized single etch step grating coupler is −2.16 dB with 3 dB bandwidth of 64 nm. It is also shown by simulations that coupling loss as low as −0.42 dB is predicted for a modified coupler structure with bottom mirror. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>